Effects of oxygen concentration on the macroscopic characteristic indexes of high-temperature oxidation of coal. Issue 3 (June 2019) - Li, Haitao; Chen, Xiaokun; Shu, Chi-Min; Wang, Qiuhong; Ma, Teng; Laiwang, Bin
Abstract: To explore the macroscopic characteristic indexes for oxidation of coal under high-temperature conditions, an XKGW-1-type high-temperature-programmed heating experimental system was constructed. Tests on high-temperature oxidation of coal under high-temperature conditions at five oxygen concentrations of 21, 17, 13, 8, and 3 vol% were independently conducted. Laws of variation in high-temperature oxidation of coal indices, such as the coal temperature, gas ratios, rate of oxygen consumption, and exothermic strength from indoor temperature to 500 °C, were investigated at those oxygen concentrations. The results showed that the variation tendencies of characteristic indices for high-temperature oxidation of coal at different oxygen concentrations were extremely intricate. At the five oxygen concentrations, the rate of oxygen consumption increased rapidly with an increase in coal temperature and eventually remained at a higher range. The rate of oxygen consumption increased with temperature with an approximate exponential trend at the five oxygen concentrations tested. For the same coal temperature, the rate of oxygen consumption decreased with the oxygen concentration. The variation tendencies of the CO and CO2 production rates were similar, both increased rapidly with an increase in coal temperature in the early stages and reached a maximum at a coal temperature of 380 °C. They decreased slightly with an increase in coal temperature at first and increased promptly thereafter. The concentrations of CH4, C2 H4, and C2 H6 first increased with an increase in the coal temperature and markedly decreased after the maximal value. The temperatures for the extreme points were 480, 410, and 420 °C for CH4, C2 H4, and C2 H6, respectively. The trends of the macroscopic characteristic indexes throughout the process of high-temperature oxidation of coal in a certain temperature range at various oxygen concentrations can be used for temperature prediction and fire prevention during coal mining. Highlights: An XKGW-1-type high-temperature-programmed heating experimental system was designed and constructed. The rate of oxygen consumption increased with temperature in an approximate exponential trend and a lower oxygen concentration had a suppressive effect on high-temperature oxidation of coal. The influence tendency for oxygen concentration on the production rate of CO and CO2 was the same as the early stage but opposite in the later period. A reliable model to evaluate the relationship between hydrocarbon generation and gas ratios against coal temperature was established. Indexes for predicting high-temperature oxidation of coal were analyzed.